PENINGKATAN KETERAMPILAN VOKASIONAL PEMBUATAN GIFT PIGURA BUNGA MELALUI METODE TASK ANALYSIS PADA SISWA LOW VISION DI SLB A YAPTI MAKASSAR - Nor Azilah, Arni; Kasmawati, Sitti; Zulfitrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the limited variety of vocational skills learning provided to low-vision students at SLB A YAPTI Makassar. Based on the observation results, students still have difficulty following the sequence of work steps, require direction and repetition at each stage, are less careful in compiling materials, and have not been able to complete the product independently. This condition indicates the need for the implementation of a more structured and gradual learning method according to the characteristics of student learning. This study aims to determine the initial ability of vocational skills in making flower frame gifts, describe the process of implementing the task analysis method, and determine the improvement of vocational skills after the method is applied to low-vision students at SLB A YAPTI Makassar. This study uses a quantitative approach with a descriptive quantitative research type. The subject of the study was a low-vision student in grade IX at SLB A YAPTI Makassar. The data collection technique used a performance test consisting of a pretest and posttest, while data analysis was carried out descriptively quantitatively by comparing the test results before and after treatment. The results showed that the initial ability of students' vocational skills was in the less skilled category. After the application of the task analysis method, the students' abilities increased to the highly skilled category. This improvement is seen in the ability to follow the sequence of work steps, use tools and materials correctly, arrange materials more carefully, and complete the creation of flower gift frames more independently. Based on the results of the study, it can be concluded that the task analysis method is effective in improving vocational skills in making flower gift frames in low vision students at SLB A YAPTI Makassar. This method helps students understand each stage of the work systematically, thereby increasing accuracy, independence, and product quality.